Effects of cultural tightness-looseness and social network density on expression of positive and negative emotions: A large-scale study of impression management by Facebook users - LIU, Pan (Institutional Knowledge at Singapore Management University, 2018)
Using data from 13,789 Facebook users across U.S. states, this study examined the main effects of societal-level cultural tightness–looseness and its interaction effects with individuals’ social network density on impression management (IM) in terms of online emotional expression. Results showed that individuals from culturally tight (vs. loose) states were more likely to express positive emotions and less likely to express negative emotions. Meanwhile, for positive emotional expression, there was a tightness–looseness by social network density interaction effect. In culturally tight states, individuals with dense (vs. sparse) networks were more likely to express positive emotions, while in culturally loose states this pattern was reversed. For negative emotional expression, however, no such interaction was observed. Our findings highlight the influence of cultural norms and social network structure on emotional expressions as IM strategies.